The protective role of Helicobacter pylori neutrophil-activating protein in childhood asthma - Karakullukcu, A.; Tokman, H. B.; Nepesov, S.; Demirci, M.; Saribas, S.; Vehid, S.; Kocazeybek, B. (Elsevier Espana Slu, 2017)
Background: Helicobacter pylori quantity and HP-NAP gene expression were evaluated in the faeces of healthy and asthmatic children. Methods: H. pylori DNAs and RNAs were isolated from the stool samples of 92 asthmatic children (AC; 3-8 years) and 88 healthy controls (HC). Quantitative PCR was used to determine the quantity of H. pylori and HP-NAP expression relative to the 16S rRNA (reference gene). Gene expression was analysed using the delta delta-Ct method. Results: H. pylori DNA was detected in the stool samples of 18 (20.4%) of the 88 HC (p <0.0001, OR= 0.79) and none of AC. No meaningful statistical differences were found between individuals with positive and negative family histories for asthma in AC and HC (p>0.05). H. pylori quantity was higher in seven of 18 H. pylori-positive samples, but HP-NAP expression levels were low in four of these seven samples. Based on a multivariate logistic regression analysis of these three variables together, only males displayed a significant difference based on gender differences (p <0.02) and it was determined that, based on the OR value of 0.46 and the 95% CI range of 0.241-0.888, male gender was an independent protective factor in asthma. Conclusions: HP-NAP levels vary to the relative concentrations of bacteria in the stationary or late logarithmic phases. Different napA expression levels may be caused by different endogenous napA gene expression or different environmental conditions. (C) 2017 SEICAP. Published by Elsevier Espana, S.L.U. All rights reserved.
Keywords: Neutrophil-activating protein; Heticobacter pylori; Asthmatic children; NAP expression; Hygiene hypothesis